Nutrition and taste and smell dysfunction - Jonathan C. Kershaw (KeAi Communications Co., Ltd., 2018)
Food selection plays a pivotal role in maintaining adequate nutrient intake, thus elucidating drivers of food choice is a meaningful strategy to maintain health and manage disease. Taste and smell are key determinants of food choice and warrant careful consideration. In this review, we first discuss how sensory stimulation influences food selection and metabolism. We then review the evidence regarding the relationship between taste and smell dysfunction and food preferences and selection, with attention given to contexts of certain chronic diseases. We conclude with brief recommendations for the management of chemosensory disorders. While sensory abilities influence food selection, the effect of taste and smell dysfunction on long-term consumption patterns and health status must be considered in light of environment, exposure, and culture. Keywords: Nutrition, Taste and smell, Sensory systems, Food choice